Triage Management of Trauma Patients Among Hospitals in The 5th District in Camarines Sur, Philippines : Intervention for Rapid Assessment and Care - Joyce N. Olea; Jane M. Tagum-Briones; Cyril B. Romero; Carlen Lagyap De Villa (The Indonesian Institute of Science and Technology Research, 2025)
This study aimed to assess the triage management of trauma patients among hospitals in the 5th District of Camarines Sur, Philippines, focusing on the interventions practiced by triage management team members and the relationship between their profiles and applied strategies. Employing a quantitative descriptive research design, data were collected through a validated questionnaire checklist administered to selected triage personnel. Statistical tools such as percentage technique, weighted mean, and chi-square test were utilized to analyze and interpret the data systematically. The findings revealed that hospitals have begun integrating strategic plans to equip triage personnel with essential knowledge and skills, thereby reducing the risks of overtriage and undertriage. Results also emphasized the importance of adopting standardized protocols and the need for a more comprehensive and evidence-based definition of trauma patients requiring specialized care. Furthermore, the study highlighted the significance of emergency preparedness—particularly during mass casualty incidents—through effective personnel deployment and structured triage systems. The introduction of an intervention-based triage management guide was found to enhance decision-making processes and patient prioritization. Future research is recommended to explore the long-term effectiveness of standardized triage training programs, as well as the development of region-specific protocols that consider local healthcare capacities, infrastructure, and challenges. Continued efforts in triage innovation and training evaluation are essential to advance trauma care practices and improve patient outcomes in diverse healthcare settings.